A Tribute to the Remaining Makyong Performers of Yala, South Thailand | Sanjungan Untuk Para Penggiat Makyong di Yala, Selatan Thailand - Tan, Sooi Beng; Shafii, A. S. Hardy (SEAMEO Regional Centre for Archaeology and Fine Arts (SPAFA), 2021)
Makyong is a form of Malay dance-theatre that combines dance, music, drama and comedy. It is said to have originated in the kingdom of Patani and later spread to Kelantan, Perlis, northern Sumatra and the Riau Islands. In the past, Makyong was performed to give thanks for a good harvest and for ritual healing. While there were more than ten active groups in the twentieth century, there is no permanent group left in South Thailand today. This essay honours the remaining performers who still come together to perform Makyong when there is an invitation. Based on oral interviews, we document the lives of the veteran performers, particularly the female actresses who played the leading roles. Through observations of their performances, we show how the Makyong performers in south Thailand have adapted some elements of Thai theatre.